2019
DOI: 10.1186/s12887-019-1405-y
|View full text |Cite
|
Sign up to set email alerts
|

Nonsynostotic plagiocephaly: a child health care intervention in Skaraborg, Sweden

Abstract: BackgroundThe aim was to evaluate the intervention’s effect on prevention and reversal of nonsynostotic plagiocephaly.MethodsThirty-eight intervention group nurses were educated about nonsynostotic plagiocephaly and asked to follow guidelines; 18 control group nurses were not. In a longitudinal single-blinded clinical intervention, parents brought infants to well-child visits according to the national schedule. Cranial shape was assessed in 176 intervention and 92 control group infants at 2-, 4-, and 12-month … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Additionally, preterm infants go through a long period of hospital care before their discharge home, and if no attention is paid to varying the head position from early on in the neonatal intensive care unit (NICU), preterm infants frequently develop DP [19,20,21]. If preventive and proactive positioning advice in infant care and handling are provided to the guardians early enough, at least the most severe forms of DP can be prevented in term or near-term newborns infants [3,7,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, preterm infants go through a long period of hospital care before their discharge home, and if no attention is paid to varying the head position from early on in the neonatal intensive care unit (NICU), preterm infants frequently develop DP [19,20,21]. If preventive and proactive positioning advice in infant care and handling are provided to the guardians early enough, at least the most severe forms of DP can be prevented in term or near-term newborns infants [3,7,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Adopting these recommendations may lead to a reduction in the prevalence of DP. It has been demonstrated that education provided by healthcare professionals, such as health visitors, midwives and nurses, can successfully reduce the prevalence of DP [58]. Alternative strategies for mitigating the impact of DP, such as helmeting therapy, are costly to individuals and healthcare systems and may be associated with morbidity [59].…”
Section: Evidence-based Recommendationsmentioning
confidence: 99%
“…within the first weeks of life) (Ellwood et al, 2020). Indeed, when parents of newborns are made aware that prevention strategies exist, their babies are two to four times less likely to develop DP (Aarnivala et al, 2015; Cavalier et al, 2011; Lennartsson & Nordin, 2019; Leung et al, 2018), and the costs associated with diagnosis and treatment, which vary between $1495 and $5195 US, can be avoided (Watt et al, 2022).…”
Section: Introductionmentioning
confidence: 99%